2012
DOI: 10.3389/fpsyg.2012.00468
|View full text |Cite
|
Sign up to set email alerts
|

The Movement Kinematics and Learning Strategies Associated with Adopting Different Foci of Attention during Both Acquisition and Anxious Performance

Abstract: Research suggests that implicit strategies adopted during learning help prevent breakdown of automatic processes and subsequent performance decrements associated with the presence of pressure. According to the Constrained Action Hypothesis, automaticity of movement is promoted when adopting an external focus of attention. The purpose of the current experiment was to investigate if learning with an external focus of attention can enhance performance under subsequent pressure situations through promoting implici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
4
19
0
2
Order By: Relevance
“…In line with this suggestion, previous literature [ 20 ] indicates that adopting an environmental focus (i.e., a focus that is outside of the body, but not explicitly centered toward the effects of a movement e.g., focusing on an auditory tone, focusing on footwear colour and its contact with the ball) results in greater performance compared to adopting an internal FOA. In a similar vein, Lawrence et al, [ 22 ] reported that under both internal and external FOA conditions participants create a comparable number of explicit cues/rules regarding the movement technique. The performance benefits of adopting an external FOA in Lawrence et al, [ 22 ] were attributed to these explicit cues/rules being environmental focused and not body centered (thus preventing the constraining processes proposed within the CAH) in the external FOA condition.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In line with this suggestion, previous literature [ 20 ] indicates that adopting an environmental focus (i.e., a focus that is outside of the body, but not explicitly centered toward the effects of a movement e.g., focusing on an auditory tone, focusing on footwear colour and its contact with the ball) results in greater performance compared to adopting an internal FOA. In a similar vein, Lawrence et al, [ 22 ] reported that under both internal and external FOA conditions participants create a comparable number of explicit cues/rules regarding the movement technique. The performance benefits of adopting an external FOA in Lawrence et al, [ 22 ] were attributed to these explicit cues/rules being environmental focused and not body centered (thus preventing the constraining processes proposed within the CAH) in the external FOA condition.…”
Section: Discussionmentioning
confidence: 86%
“…In a similar vein, Lawrence et al, [ 22 ] reported that under both internal and external FOA conditions participants create a comparable number of explicit cues/rules regarding the movement technique. The performance benefits of adopting an external FOA in Lawrence et al, [ 22 ] were attributed to these explicit cues/rules being environmental focused and not body centered (thus preventing the constraining processes proposed within the CAH) in the external FOA condition. Whilst the current experiment did not measure the number or type of explicitly generated cues/rules, it is possible that the benefits of the Colour condition over that of the IFOA condition are due, in part, to this effect.…”
Section: Discussionmentioning
confidence: 86%
“…We studied golf putting because it has proved to be sensitive to attentional focus manipulations, and it has been investigated frequently in studies on the effect of focus changes on performance (e.g., Bell & Hardy, 2009;Land & Tenenbaum, 2012;Lawrence, Gottwald, Khan, & Kramer, 2012;S. M. Weiss, Reber, & Owen, 2008;Wulf, Lauterbach, & Toole, 1998;Wulf & Su, 2007).…”
mentioning
confidence: 99%
“…Previous studies have showed that instructions inducing external focus of attention can benefit learning when compared to internal focus, in different populations and tasks [10][11][12][13][14] ; however, studies with children are incipient. Several reasons can explain the lack of interest in this population.…”
Section: Introductionmentioning
confidence: 96%